Effets d`un entraînement simulé à basse et en haute altitude sur les aptitudes physiques de boxeurs adolescents - Wang, Y.; Fu, B.; Gao, Y. (Science & Sports, 2024)
Background This study aimed to determine the effects of high-altitude living low-altitude training on the athletic performance and metabolic indexes of adolescent boxers by using a hypobaric cabin to simulate hypoxia in high-altitude environments.